Estimationof Biomass and Carbon Sequestration by Non-Destructive Method in Dry Deciduous Forest of Shivpuri, Madhya Pradesh, India. Issue 1 (December 2021) - Bung, S; Rajmohan, S; Bhutia, S; Pandey, H; Mitra, M
Abstract: The study aims to assess the plant biomass and carbon storage potential of the forests of Shivpuri, Madhya Pradesh, India. The study was carried out in Satanwada Range in Shivpuri Forest Division. A total of 96 quadrats of 10×10 m 2 were laid. The non-destructive algometric method was used to estimate carbon sequestration. The results show that Acacia catechu (202 individuals/ha) dominated the forest, followed by Anogeissus pendula (90 individuals/ha). The total biomass of the forest was estimated to be 34.72±0.41t/ha, with Boswellia serrata (7.943t) recording the highest. The minimum biomass was recorded for Grewia sp (0.06t). The highest carbon content was found in B. serrata (3.97t; 25 individuals) followed by A. Catechu (2.92t; 195 individuals). Although A. catechu was dominant in the area, due to its lower girth class and young age, the net carbon storage was less than that of B. serrata . It was found that plots with higher carbon stock had higher species richness than plots composed of single species. Therefore, plantations of mixed native species should be preferred for future restoration activities as they are more efficient in sequestrating carbon than monoculture plantations.